The relationship of teacher leadership towards social relationship and stutter student's performance in Punjab, Pakistan - Iqbal, Faiza (2020)
There are various problems faced in the Department of Education in Pakistan especially among stuttering students such as lack of social relationships, bullying, poor performance in the classroom, teachers unable to manage classes efficiently, lack of motivation to teach and unable to teach effectively. Therefore, research should be done to understand and manage the problem. Moreover, based on the theory of distributive leadership, social interaction and social cognitive, this study examined the relationships between teacher leadership and social relations moderation variables on the performance of stuttering students in Pakistan. This quantitative study used instruments such as demographic information, teacher leadership scale, social relationship scale and stuttering student performance scale. A total of 584 teachers from schools around the East Punjab province of Pakistan were selected through Proportionate Stratified Sampling. Descriptive statistics, t-test and smart PLS (Partial Least Square) were used to analyze the data based on the objectives of the study. The results showed that all teachers had self-resilience, and different leadership styles at a moderate level. Construct variation based on teacher leadership in social activities had significant differences in teacher emotional intelligence and leadership style, while gender had a significant relationship between teachers and students with two significant differences occurring in religion and ethnicity. Distributive leadership in this study included formal and informal teacher leadership that can play an important role in teachers and hence student success. In terms of relationships, the findings found that the moderating effect of social relationships between teacher leadership and stuttering student performance was weak. The conclusion of this study indicated that teacher leadership for student activities can improve the performance of students who stutter in the classroom. From these findings, in order to improve teacher leadership and teaching effectiveness, social relationship should enhance teachers’ capabilities in classroom management strategies and develop their intrinsic motivation in teaching.